2020
DOI: 10.3390/cells9010211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative In-Depth Analysis of the Mouse Mast Cell Transcriptome Reveals Organ-Specific Mast Cell Heterogeneity

Abstract: Mast cells (MCs) are primarily resident hematopoietic tissue cells that are localized at external and internal surfaces of the body where they act in the first line of defense. MCs are found in all studied vertebrates and have also been identified in tunicates, an early chordate. To obtain a detailed insight into the biology of MCs, here we analyzed the transcriptome of MCs from different mouse organs by RNA-seq and PCR-based transcriptomics. We show that MCs at different tissue locations differ substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 62 publications
(105 reference statements)
2
52
0
1
Order By: Relevance
“…In contrast, the lack of chymase/mMCP-4 significantly reduced the infiltration of mast cells in the inflamed joint in a collagen-induced arthritis model [54], and in a model of bleomycin-induced lung inflammation, the mast cell numbers were increased in the mMCP-4 −/− mice [55]. In the mouse small intestine, the submucosal mast cell counts is normally very low (<1 mast cell per 100 villi) [56], and the low numbers of submucosal mast cells are confirmed by the low numbers of mast cell protease transcriptional reads ( [44] and Lars Hellman, personal communication). During infections with Giardia and other intestinal parasites, submucosal mast cell counts increase ( [23][24][25]57,58] and current study).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the lack of chymase/mMCP-4 significantly reduced the infiltration of mast cells in the inflamed joint in a collagen-induced arthritis model [54], and in a model of bleomycin-induced lung inflammation, the mast cell numbers were increased in the mMCP-4 −/− mice [55]. In the mouse small intestine, the submucosal mast cell counts is normally very low (<1 mast cell per 100 villi) [56], and the low numbers of submucosal mast cells are confirmed by the low numbers of mast cell protease transcriptional reads ( [44] and Lars Hellman, personal communication). During infections with Giardia and other intestinal parasites, submucosal mast cell counts increase ( [23][24][25]57,58] and current study).…”
Section: Discussionmentioning
confidence: 98%
“…The chymase mMCP-4 is only significantly expressed by the connective tissue mast cells (CTMCs) (see reference [44] and Immgen.org), and the knockout of mMCP-4 did not affect the storage and expression of other mast cell proteases [45]. This stands in contrast to the knockout of mMCP-5, which affected the storage and activity of carboxypeptidase A3 [46] and vice versa, the knockout of CPA3 affected the storage and activity of mMCP-5 [47].…”
Section: Discussionmentioning
confidence: 99%
“…About 5% of the genome encodes information on human MC proteases, and the protease mRNA content is comparable to the content of housekeeping genes transcripts. This re ects the high content of proteases in the cytoplasm of MC 7,15,[35][36][37][38][39] .…”
Section: Additional Criteria For Mastocytosis: Cytotopography Of Procmentioning
confidence: 99%
“…[3][4][5] . A special characteristic of the biology of MCs is the high presence of proteases in comparison with other immunocompetent cells 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Chymases belong to the large family of serine proteases, and their expression is essentially unique to mast cells [11-13]. Mast cells can express high levels of chymase-encoding mRNA, previous findings having revealed that up to 2.5% of the total mRNA pool in mast cells can code for chymases [13, 14]. Notably, chymase expression in mast cells is constitutive and in most cases not affected to any major extent by mast cell activation [10].…”
Section: Introductionmentioning
confidence: 99%